2009
DOI: 10.1002/ijc.24396
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling during rat mammary carcinogenesis induced by 7,12‐dimethylbenz[a]anthracene

Abstract: 7,12-Dimethylbenz[a]anthracene (DMBA)-induced rat mammary carcinoma is a well-recognized model; however, the genetic alterations during its carcinogenesis have yet to be determined. We used laser capture microdissection to specifically isolate cells from terminal end buds (TEBs), the origin of carcinoma, at 2 weeks after sesame oil treatment (control) or DMBA treatment (DMBATEBs), ductal carcinoma in situ (DCIS) and invasive mammary carcinoma (MC). Using an oligonucleotide microarray representing 20,600 rat pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Another study reported PCP4/PEP19 expression in normal and neoplastic human adrenocortical tissue where it increases aldosterone production [13, 14]. Our previous study showed that PCP4/PEP19 expression was increased in the mammary gland tissue of rats in which carcinogenesis was induced by exposure to 7, 12-dimethylbenz [a] anthracene exposure [15]. We also detected PCP4/PEP19 expression in human breast cancer and found that it exerts anti-apoptotic functions in human breast cancer cell lines via CaMKK and Akt signaling pathways [16].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported PCP4/PEP19 expression in normal and neoplastic human adrenocortical tissue where it increases aldosterone production [13, 14]. Our previous study showed that PCP4/PEP19 expression was increased in the mammary gland tissue of rats in which carcinogenesis was induced by exposure to 7, 12-dimethylbenz [a] anthracene exposure [15]. We also detected PCP4/PEP19 expression in human breast cancer and found that it exerts anti-apoptotic functions in human breast cancer cell lines via CaMKK and Akt signaling pathways [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated PCP4/PEP19 expression in the normal and neoplastic human adrenocortical tissues, acting as a regulator of aldosterone production [13, 14]. However, an association between PCP4/PEP19 expression and cancer cell apoptosis has not been fully investigated yet and is largely disregarded in current discussion, even though our previous study showed that PCP4/PEP19 expression in the mammary gland tissue was significantly increased during rat carcinogenesis stimulated by 7, 12-dimethylbenz [a] anthracene (DMBA) exposure [15]. The expression of PCP4/PEP19 was significantly induced in the terminal end buds where mammary gland carcinoma develops, and the expression levels increased as cancer progressed from ductal carcinoma in situ to invasive ductal carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…The forward and reverse primers for detection of target genes in myometrium were as follows: PCP4/PEP-19, 5 0 -GCGCGGATCCATGAGTGAGCGACAAGGTGC-3 0 and 5 0 -GGCCGTCGACCTAGGACTGACACCCAGCC-3 0 ; neuromodulin (GAP-43), 5 0 -GCAATGTTCCGTTCATCTGA-3 0 and 5 0 -CCTTAGAGCCGCAAGTTTAC-3 0 ; neurogranin (RC3), 5 0 -CACCCAAGCACACTCACTTA-3 0 and 5 0 -AACAACCC-TCTTCCCTTCATC-3 0 ; GAPDH, 5 0 -AGGGCTGCTT-TAACTCTG-3 0 and 5 0 -CTGGAAGATGGTGATGGG-3 0 . The PCR amplification was programmed as follows: denaturing at 95 C for 30 seconds, annealing at 50 C for 30 seconds (60 C for PCP4/PEP- 19), and extension at 72 C for 30 seconds. The PCR was terminated after 30 cycles.…”
Section: Semiquantitative Pcrmentioning
confidence: 99%
“…16 PCP4/PEP-19 was also induced in models of cardiac hypertrophy 17 and altered in several cancers. [18][19][20][21][22] At the cellular level, PCP4/PEP-19 has broad effects on diverse processes, including neurite outgrowth, 23 premature neuronal differentiation, 24 long-term plasticity at neuronal synapses, 25 altered cardiac excitability and contractility, 26 and antiapoptotic activity. 27,28 PCP4/PEP-19 expression was also shown to protect against Ca 2þ overload 28 and sensitize cells to adenosine triphosphate (ATP)-dependent Ca 2þ release.…”
Section: Introductionmentioning
confidence: 99%